2018
DOI: 10.3892/ol.2018.7986
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of TRPV1 receptors by TNF‑α orchestrates the development of vincristine‑induced pain

Abstract: Vincristine is one of the most common anticancer drugs clinically employed in the treatment of various malignancies. A major side effect associated with vincristine is the development of neuropathic pain, which is not readily relieved by available analgesics. Although efforts have been made to identify the pathogenesis of vincristine-induced neuropathic pain, the mechanisms underlying its pathogenesis have not been fully elucidated. In the present study, a neuropathic pain model was established in Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Inflammatory mediators, such as IL-1β (Binshtok et al, 2008; Stemkowski et al, 2015; Alles and Smith, 2018) and TNFα (Czeschik et al, 2008; Leung and Cahill, 2010; Wang et al, 2018), that are induced in EAE (Melanson et al, 2009; Rodrigues et al, 2016) can modulate ion channel expression and/or activity and induce neuronal hyperexcitability. The electrophysiological changes remaining into the chronic phase of MOG-EAE suggest that transient immune cell infiltration and activation in the DRG inherently alters neuronal properties into the chronic phase of MOG-EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators, such as IL-1β (Binshtok et al, 2008; Stemkowski et al, 2015; Alles and Smith, 2018) and TNFα (Czeschik et al, 2008; Leung and Cahill, 2010; Wang et al, 2018), that are induced in EAE (Melanson et al, 2009; Rodrigues et al, 2016) can modulate ion channel expression and/or activity and induce neuronal hyperexcitability. The electrophysiological changes remaining into the chronic phase of MOG-EAE suggest that transient immune cell infiltration and activation in the DRG inherently alters neuronal properties into the chronic phase of MOG-EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy-induced peripheral sensory neuropathy is linked to the sensitisation of TRPV1 (e.g., Wang et al, 2018b) and TRPV1 is also overexpressed following nerve damage in the oral cavity (e.g., Yilmaz et al, 2007). Finally, it has been suggested that metal mouth can be explained by the retronasal activation of olfactory epithelium (e.g., Omur-Ozbek et al, 2012), perhaps due to an intra-oral over-production of metallic volatiles, although a source for these metallic volatiles in chemotherapy has yet to be identified (e.g., Mirlohi et al, 2015), and it is not clear which congruent stimulus (Lim & Johnson, 2011;Lim & Johnson, 2012) 4.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does oxidative stress sensitise TRPV1 (Chuang & Lim, 2009), but at least three chemotherapy drugs-oxaliplatin, paclitaxel, and vincristine-have been found to sensitise TRPV1, markedly heightening capsaicin responses in dorsal root ganglia (see Figure 7) (Anand, Otto, & Anand, 2010;Li et al, 2015;Wang et al, 2018b). There may be a link to inflammatory activation via interplay with TLR4 (Li et al, 2015) and TNF-α (Wang et al, 2018b). Researchers have notto the best of our knowledge-investigated whether TRPV1 sensitisation also occurs in the oral cavity during chemotherapy.…”
Section: Trpv1 and Metalsmentioning
confidence: 99%
“…The XRD patterns in Fig. 2d) also exhibited a small peak of metallic Ag at 38.8 and 44.9 2ϴ in its cubic and wurtzite phase; this indicate that ZnO-Ag nanopar ticles were completely formed 16,17 . Fig.…”
Section: Phase Identificationmentioning
confidence: 90%